Spatial Planning for a Sustainable Singapore - Wong, Tai-Chee.; Yuen, Belinda; Goldblum, Charles; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
The book is intended to be a landmark publication to showcase Singapore academics' and practising planners' work and thinking in the globalisation age. The book takes a reflective approach in reviewing the direction, impact and significance of sustainable development in Singapore planning and the future challenges facing the city-state looked upon by many developing countries as a 'model'. The book analyses and provides an insight to Singapore's planning system and practices associated with sustainable development. It contributes and produces an impact on urban planning literature in a renewed perspective about Singapore that reflects the reality and need to address sustainability in the triangular relationship of economic, environmental and social developments. Audience: University libraries, students and government agencies with an interest in understanding the rationale of policy formation, planning system and its implementation in Singapore.
Global Development and Planning -- Sustainability Planning and Its Theory and Practice: An Introduction -- Planning the World Metropolis on an Island-City Scale: Urban Innovation as a Constraint and Tool for Global Change -- Sustainable City Centre Development: The Singapore City Centre in the Context of Sustainable Development -- Integrated Resort in the Central Business District of Singapore: The Land Use Planning and Sustainability Issues -- Singapore River: Six Strategies for Sustainability -- Transport, Industrial, Housing and Nature Planning -- Singapore's Urban Transport: Sustainability by Design or Necessity? -- Achieving Sustainable Industrial Development Through a System of Strategic Planning and Implementation: The Singapore Model -- Public Housing in Singapore: A Sustainable Housing Form and Development -- Vertical Living and the Garden City: The Sustainability of an Urban Figure -- Nature and Sustainability of the Marine Environment -- Singapore's Natural Environment, Past, Present and Future: A Construct of National Identity and Land Use Imperatives -- Conclusion: Beyond Sustainable Development?.
Keywords: GEOGRAPHY; REGIONAL PLANNING; ARCHITECTURE; NATURE CONSERVATION; GEOGRAPHY; LANDSCAPE/REGIONAL AND URBAN PLANNING; URBANISM; NATURE CONSERVATION; CITIES, COUNTRIES, REGIONS